Designing Aircraft Simulators - Yurkov, Nikolay Kondratyevich; Romancheva, Nina Ivanovna; Zatuchny, Dmitry Alexandrovich; Goncharov, Evgeny Yuryevich (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book presents the design of modular architecture flight simulators. Safe transportation of people and goods is one of the main directions for the development of the world economy. At the same time, in conditions of constantly increasing intensity of air traffic, the actions of people, responsible for piloting aircraft and air traffic control are of particular importance. In this regard, special attention should be paid to the process of training such specialists. This book describes various flight simulators of an aircraft, as well as to assess the impact of various characteristics of aviation simulators on the quality of skills of aviation specialists. The book discusses the following issues: 1) method of setting dynamic parameters; 2) methods of correction of simulator parameters, according to expert opinions of operating organizations; 3) modules of simulators of operation of various aircraft units and flight conditions; 4) prospects for the development of aviation simulators; 5) collection and evaluation of information in the process of training on aviation simulators.
Introduction -- Chapter 1: The state and prospects of development of aviation simulator construction -- Chapter 2: Complex simulators of transport aircraft -- Chapter 3: Identification of systems and control tasks in the development of aviation simulators -- Chapter 4: Some issues of practical development of flight dynamics simulators -- Chapter 5: Creation of a virtual educational environment for training air traffic dispatchers.
Keywords: Aerospace engineering; Astronautics; Computer simulation; Signal processing; Aerospace Technology and Astronautics; Computer Modelling; Signal, Speech and Image Processing .